2021
DOI: 10.1186/s13023-020-01630-2
|View full text |Cite
|
Sign up to set email alerts
|

Liver manifestations in a cohort of 39 patients with congenital disorders of glycosylation: pin-pointing the characteristics of liver injury and proposing recommendations for follow-up

Abstract: Background The congenital disorders of glycosylation (CDG) are a heterogeneous group of rare metabolic diseases with multi-system involvement. The liver phenotype of CDG varies not only according to the specific disorder, but also from patient to patient. In this study, we sought to identify common patterns of liver injury among patients with a broad spectrum of CDG, and to provide recommendations for follow-up in clinical practice. Methods Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Elevated serum transaminases observed in the majority of our CDG patients were associated with the presence of coagulation disorders, including protein C, protein S, and antithrombin deficiency. Similar observations were reported by Starosta et al ( 13 ). However, only two patients developed thrombotic events.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Elevated serum transaminases observed in the majority of our CDG patients were associated with the presence of coagulation disorders, including protein C, protein S, and antithrombin deficiency. Similar observations were reported by Starosta et al ( 13 ). However, only two patients developed thrombotic events.…”
Section: Discussionsupporting
confidence: 93%
“…In the recently published paper on liver manifestations in 39 CDG patients, Starosta et al found that 48.6% of those persons had elevated values of alanine aminotransferase and 70.3% of them had elevated values of aspartate aminotransferase ( 13 ). These parameters mostly increased during the first 5 years of life in most types of CDG (apart from ALG8-CDG, CCDC115-CDG, MPI-CDG, PGM1-CDG, and TMEM165-CDG patients), but they improved significantly afterwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver disease is highly penetrant in CDG, and all patients require screening for hepatic injury via physical examination, laboratory investigations, and liver imaging 2 . The most frequent serum markers of liver injury are elevated TAs, which improve spontaneously with age in most type I CDG 2 .…”
Section: Monitoring and Managementmentioning
confidence: 99%
“…Liver disease is highly penetrant in CDG, and all patients require screening for hepatic injury via physical examination, laboratory investigations, and liver imaging 2 . The most frequent serum markers of liver injury are elevated TAs, which improve spontaneously with age in most type I CDG 2 . Gamma‐glutamyl transferase (GGT) and alkaline phosphatase (AP) are elevated in some cases, and ceruloplasmin and copper levels are altered in some CDG, as presented in Table 1.…”
Section: Monitoring and Managementmentioning
confidence: 99%